Analisis Perkembangan Tokpedia Dan Gojek Pasca Merger Sebagai Goto Dan Kolaborasinya Dengan Tiktok Terhadap Perekonomian - Mhd. Dimas Septiandy; Nabila Hamim; Nurbaiti Nurbaiti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Digital business is starting to become the most popular business activity. The reason is that people continue to try to adapt to the sophistication of technology in this digital era to make it easier to do their work. Ease of carrying out digital buying and selling transactions is now available in GoTo, a company resulting from the merger of Gojek and Tokopedia. GoTo is a forum and provides access for entrepreneurs, especially MSMEs, to open businesses and sell online. Apart from making it easier for people to do business and shop, Goto also has a positive impact on the development of the Indonesian economy. Tiktok is also an online platform that influences the development of Tokopedia. Tiktok not only accommodates Tokopedia product branding but is now also one of the sales channels for Tokopedia products on its TikTokshop page. This invites high enthusiasm from economic actors. This research was conducted to find out how GoTo developed after the merger and the influence of the Tiktok and Tokopedia collaboration on the Indonesian economy. The method used is descriptive qualitative so that the data collected is correct based on literature reviews and scientific publications.